Ghana : Country Procurement Assessment Report, Volume 2. Main Report - World Bank (Washington, DC, 2013)
This report highlights a broad array of poor procedures and practices throughout the tendering and contract management process, which have been the cause of many of Ghana's public procurement problems, and where most of the leakages in public procurement funding occur and substantial savings could be realized. Most of the procedural anomalies are now being corrected by the Public Procurement Act (PPA), which includes the new regulations for the procurement of goods, works, and consulting services to be applied by all Procurement Entities. The provisions for standard tender documents and standard request for consulting proposals being completed, will detail the general principles embedded in the PPA, including evaluation and selection criteria. Standard contract documents, also being completed, will streamline current problems with contracting and payment procedures, labor standards, and dispute resolution. Good procurement manuals and training should leave no room for lack of understanding by procurement staff. The positive results on the ground depend largely on how well the new policies are put into practice and the extent to which this is done without political interference to the contrary. The application of the PPA and the Standard Tender and Contract Documents will not be successful without a broad training and "refresher" program and encouragement of officials in charge of procurement. Oversight and review functions are critical to exercising good procurement fiduciary management and Ghana is taking the necessary measures to strengthen it. Some recommendations include improving procurement planning and budgeting; value for money; contract management; stores management, record keeping, ensuring use of modern labor standards in works contracts, securing as soon as possible the necessary external financing for training, developing clear procedures for the prior and post review of procurement activities, putting in place an effective sanctions system; having competent experts do procurement audits separately, providing for capacity building, enforcing the code of conduct for civil servants and ethics codes, and involving the private sector and the media by making it aware of the various means in the national laws by which it can contribute to preserving transparency and accountability.